Elements of environmental contamination in the informal extraction of coal and alternatives of sustainable extraction in the district of Lucma, Gran Chimu Province La Libertad Region - Guevara Alvarado, Nicolás (2019)
In this article, the following procedures were carried out: a geological-mining evaluation, taking five water samples (A1-A5), and five soil samples (S1-S5) to define pollution levels. The results of the analysis of the water samples were checked against the environmental quality standards (ECA) of the Ministry of Environment (MINAM). Considering the analysis of water for population use, aluminum (Al) and iron (Fe) were detected as elements that have exceeded quality standards; while, in the analysis of water for animal drink and vegetable irrigation, the values ​​were below the established standards. The results, with respect to the collection of five soil samples, did not exceed the levels of the Environmental Quality Standards (ECA), because the values ​​were below the established standards. In view of the results indicated above, the Dutch regulations that consider other control parameters have been considered, these determined that there is environmental contamination in the elements of Hg, As, Cd, Co, Mo, Sb, and V. With the proper opening of underground work in apparent areas, the conservation and proper use of explosives and safety implements, with the control and minimization of particulate material, the marketing of coal properly and the rigid control of ore will be achieved, establish a sustainable and responsible mining extraction. With permanent monitoring and supervision by qualified technical personnel, it will be possible to reduce and / or eliminate environmental pollution in water, soil and in informal mining activity.